Atividade alelopática, antioxidante e antimicrobiana de plantas com uso popular antimalárico - Ferrari, Ana Paula (2013)
The aim of this study was to analyze the influence of different concentrations of crude ethanol extracts (EET) and dichloromethanic (EDC) of antimalarial medicinal species Bidens pilosa L. (beggartick), Phyllanthus niruri L. (shatter stone), Petiveria alliacea L. (guinea) and Senna hirsuta L. (sicklepod) on germination (GER), mean germination time (TMG), mean speed of germination (VMG), radicle (RAD) and hypocotyls (HIP) of Lactuca sativa L. (lettuce) and Ipomoea grandifolia (Dammer) O'Donel (rope-glory). The experimental design was completely randomized, distributed in a factorial (species antimalarial vs. extractor vs. concentration). Bioassays were performed with four replicates of 25 seeds for germination tests, and 10 pre-germinated seeds for the growth bioassays. Germinated seeds were counted daily for obtaining the TMG and VMG while GER, DAR and HIP were measured after 144 hours of application of the extracts. In parallel to the study of allelopathic activity aimed also to examine the antioxidant and antimicrobial activities of EET and EDC of four malarial species used in bioassays, as well as the species Quassia amara L. (quássia amarga). Analyses antioxidants were performed through three different methodologies, namely: scavenging of ABTS•+, scavenging DPPH•, both performed with EET and EDC, and antioxidant power reduction iron (FRAP), performed with EET, as well as the content of total phenolic compounds (TCF). The EET were compared to commercial antioxidant BHT (butylated hydroxytoluene), BHA (butylated hydroxyanisole) and α-tocopherol. The results of bioassays of extracts of plants antimalarial and their respective concentrations showed inhibitory effects, and in some cases stimulatory, different magnitudes of the processes of germination and/or growth of the target species. Increasing the concentration of EET and EDC of P. alliacea and EET of S. hirsuta, did not show significant results for variables TMG, VMG and GER of corda-de-viola, and the EDC of P. alliacea also did not influence RAD HIP. The EET of B. Pilosa showed excellent results compared to inhibition of RAD and HIP lettuce and GER, TMG, VMG and RAD rope-glory, suggesting the use of this extract for future work of purification, isolation and identification of bioactive substances. In all methods of antioxidant activity analyzed, the EET of Q. amara shown as the most effective treatment, followed by EET of P. niruri, which are analyzed in High Performance Liquid Chromatography Reverse-Phase (HPLC-RP), indicating the presence of rutin, myricetin, quercetin and gallic acid for both species, these compounds being recognized for its antioxidant properties. Analyses were performed using antimicrobial minimum inhibitory concentration (MIC) of the plant extracts with concentrations between 5.0 and 0.88 mg mL-1 in 96-well microplates inoculated with Baccilus cereus ATCC 11.778. The EET of Q. amara, P. niruri and S. hirsuta and EDC of B. pilosa showed minimal inhibitory concentration (MIC) = ≤ 0.088 mg mL-1. Thus, the data presented in this study indicate the potential use of the EET of B. pilosa and EET of Q. amara as sources of molecules having herbicidal activity, antioxidants and antimicrobial properties, and these extracts are important sources for the search of molecules that can be used as a prototype for the development of new products in the agrochemical industries, food and/or pharmaceuticals, requiring future studies on the extraction, purification, isolation and identification of bioactive compounds and their mechanisms of action.